Do Pandemics Change Healthcare? Evidence from the Great Influenza - Rui Esteves; Kris James Mitchener; Peter Nencka; Melissa A. Thomasson (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using newly digitized U.S. city-level data on hospitals, we explore how pandemics alter preferences for healthcare. We find that cities with higher levels of mortality during the Great Influenza of 1918-1919 subsequently expanded hospital capacity by more than cities experiencing less influenza mortality: cities in the top half of the mortality distribution increased their count of hospitals by 8-10 percent in the years after the pandemic. This effect persisted to 1960 and was driven by increases in non-governmental hospitals. Growth responded most in richer cities, exacerbating existing inequalities in access to healthcare. We do not find evidence that government-run hospitals or other types of city-level spending related to healthcare responded to pandemic intensity, suggesting that large health shocks do not necessarily lead to increased public provision of health services.
Keywords: I11; I14; J10; N32; 330; hospitals; healthcare; influenza; pandemics; local public goods